Women's perspectives of social media for coping / Sharon Grace Kwan - Kwan, Sharon Grace (UiTM Press, 2024)
This paper analyses women's experience of consuming TikTok to cope with everyday stress. Our objectives are to examine the significant meanings of TikTok to women as a coping tool, to explore the motivations behind women's engagement with the platform for stress and emotion management, including to investigate the relationship between women's social and economic conditions and their consumption of TikTok for stress-coping. The investigation is carried out by conducting semi-structured interviews to collect qualitative data. Six women were purposively sampled from a lower-income (B40) background who all use TikTok. Our results indicate several positive outcomes in women's stress and emotion management, particularly in managing work and personal stressors when consuming TikTok. Moreover, the results revealed that TikTok does not necessarily gratifiy as a tool for social validation but rather as a tool to comprehend and cope with women's stress. Additionally, TikTok positively affects women by encouraging them to seek self-betterment through its various media channels of entertainment, information, and distraction. The implications of this paper could be used to better understand the nature of stress that women face in this current era, and how social media is capable of becoming an effective tool for stress-coping.